Future temperature and salinity in Puget Sound, Washington State, under CMIP6 climate change scenarios - Stevie Walker; Hem Nalini Mozaria-Luna; Isaac Kaplan; David Petatán-Ramírez (Journal of Water and Climate Change, 2022)
Climate change will reshape estuarine ecosystems through bottom-up and top-down processes, directly affecting species at all trophic levels. To better understand future regional climate change effects on sea surface temperature and salinity, we used empirical downscaling to derive high-resolution time series of future sea surface temperature and salinity in Puget Sound (Washington State, USA). Downscaling was based on scenario outputs of two coarse-resolution Coupled Model Intercomparison Project Phase 6 (CMIP6) general circulation models, GFDL-CM4 and CNRM-CM6-1-HR. We calculated 30-year climatologies for historical and future simulations, calculated the anomalies between historical and future projections, interpolated to a fine-resolution, and applied these downscaled anomalies to a Regional Ocean Modeling System (ROMS) time series, yielding short-term and long-term delta-downscaled forecasts. Downscaled output for Puget Sound showed temperature and salinity variability between scenarios and models, but overall, there was a strong model agreement of future surface warming and freshening in Puget Sound. Spatially, we found regional differences for both temperature and salinity, including higher temperatures in South Puget Sound and lower salinity in Whidbey Basin. Interpreting and applying downscaled CMIP6 projections of temperature and salinity will help assess climate change vulnerability and inform future ecosystem-based management decisions in Puget Sound and other coastal and estuarine systems. HIGHLIGHTS We derived temperature and salinity time series for Puget Sound from future projections through empirical downscaling.; We overlaid future anomalies over high-resolution regional sea surface temperature (SST) and salinity projections for Puget Sound.; Puget Sound showed high sensitivity to sea surface warming and freshening.; SST and salinity projections will help drive the Atlantis ecosystem model for Puget Sound.;